Principles of Real Analysis - Aliprantis (Charalambos D); Burkinshaw (Owen) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2004)
Real Analysis
41435a.jpg;41435b.jpg
22.5
Keywords: Real Analysis